Design and Analysis of Drive System with Slip Ring Induction Motor for Electric Traction in India - Nagamani Chandra sekara; Somanatham R; Chaitanya Kumar U (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
The use of Squirrel Cage for Traction has revolutionised the motive power of a Locomotive. The Asynchronous Motor is rugged with high starting Torque, has a very smooth Voltage and Speed control as compared to a DC Series Motor. When looking at the Traction perspective, a Slip Ring Induction Motor can be an alternative to the Squirrel Cage Motor as it has higher starting Torque and better efficiency than a Squirrel Cage Motor. the Slip Power Recovery scheme also plays a proactive role as ther can be substantial savings of energy in case of a Slip Ring Induction Motor. A detailed design and analysis of a Drive System with Slip Ring Induction Motor for Electric Traction is presented in this Research Paper